Dreaming of Europe: locations in a long dream series of an US American - Schredl, Michael (International journal of dream research, 2025)
Previous research has shown that traveling to new places can affect dream content and, thus, offer an opportunity to study the continuity between waking and dreaming. In the present study, a dream series (N = 2090 dreams) spanning 10 yrs. from 2013 to 2022 was analyzed. The participant (an US American) visited Europe for the first time in 2015 and a second time in 2022. As predicted, dreams with Europe was the setting increased while he was there, but even after 6 yrs. the frequency of Europe dreams was elevated in respect to baseline levels. The findings support the continuity hypothesis and demonstrated that analyzing places in dreams can further our knowledge of how dreams are linked to waking life.